2023
DOI: 10.3390/antiox12030748
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Intracellular TAGE and the TAGE–RAGE–ROS Axis in the Onset and Progression of NAFLD/NASH

Abstract: The repeated excessive intake of sugar, a factor that contributes to the onset of nonalcoholic fatty liver disease (NAFLD) and its progression to the chronic form of nonalcoholic steatohepatitis (NASH), markedly increases the hepatocyte content of glyceraldehyde (GA), a glucose/fructose metabolic intermediate. Toxic advanced glycation end-products (toxic AGEs, TAGE) are synthesized by cross-linking reactions between the aldehyde group of GA and the amino group of proteins, and their accumulation has been impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 113 publications
0
5
0
1
Order By: Relevance
“…Previous studies have suggested the involvement of TAGE accumulation in the pathogenesis of NASH, CVD, DM and its complications, some cancer types, and AD [22,23,[37][38][39]55,77]. We recently demonstrated that TAGE were produced by and accumulated in many cell types [24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Cytotoxicity Of Tagementioning
confidence: 90%
See 3 more Smart Citations
“…Previous studies have suggested the involvement of TAGE accumulation in the pathogenesis of NASH, CVD, DM and its complications, some cancer types, and AD [22,23,[37][38][39]55,77]. We recently demonstrated that TAGE were produced by and accumulated in many cell types [24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Cytotoxicity Of Tagementioning
confidence: 90%
“…The formation of TAGE mainly occurs intracellularly through glycation reactions between GA and intracellular proteins, which produce TAGE molecules of different sizes and properties. Although a more detailed understanding of the mechanisms underlying TAGE toxicity is needed, previous studies have indicated that it is due to oxidative stress-induced damage [26,39], the loss of protein functions as a result of glycation modifications [39], and TAGE aggregation and accumulation [30].…”
Section: Structures Of Tagementioning
confidence: 99%
See 2 more Smart Citations
“…(DNA-damage response, DDR), 在转录水平激活P53, 导致细胞衰老, 因此P53被视作衰老的生物标志物 [24] . 衰老过程中伴随产生的氧化应激是引起肝脏损 伤, 导致NAFLD等肝脏疾病发病的重要因素 [30] . 氧化 应激水平过高以及抗氧化酶活性的下降会导致肝细胞 的蛋白质、脂质以及核酸降解, 从而导致肝脏损伤 [31] .…”
Section: Dna在受到氧化损伤后会启动dna损伤应答机制unclassified